Sensorless fuzzy SMC for a permanent magnet synchronous motor - Mohamed, H.A.F.; Yang, S.S.; Moghavvemi, M. (2009)
This paper presents the design of a fuzzy logic sliding mode controller to control a permanent magnet synchronous motor. Fuzzy logic is introduced to the system to solve the chattering problem associated with sliding mode controllers. Based on the proposed switching surface, a switching control law that satisfies the hitting condition and guarantees the existence of the sliding mode is designed using Lyapunov theory. Then a fuzzy controller is designed based on the obtained stability conditions to decide how to activate the softening control action of the equivalent controller or the robust switching controller. To drive the motor sensorlessly, a sliding mode observer is designed. The effectiveness of the proposed controller is investigated through simulation.